Statement of ESMINT and ESNR regarding recent trials evaluating the endovascular treatment at the acute stage of ischemic stroke - Pierot, Laurent; Söderman, M.; Bendszus, Martin; White, P.; Muto, M.; Turjman, F.; Mangiafico, S.; Gralla, J.; Fiehler, J.; Szikora, I.; Cognard, C. (Neuroradiology, 2013)
Background: Three recent, simultaneous publications report the neutral results of three randomized studies (SYNTHESIS Expansion, Interventional Management of Stroke (IMS) III, and Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR RESCUE)) comparing IV thrombolysis therapy or standard care (MR RESCUE) to the endovascular treatment (EVT) of acute ischemic stroke (AIS) [1–3]. The results of these three trials might lead to the erroneous conclusion that endovascular treatment has no or little place in the management of AIS. However, careful analysis of the IMS III, SYNTHESIS, and MR RESCUE studies is mandatory prior to assessment of the value of EVT of AIS. Also, the limits of the current and future trials should be outlined.
Gesehen am 24.01.2022